2019
DOI: 10.1186/s12889-019-6849-3
|View full text |Cite
|
Sign up to set email alerts
|

What’s in it for me? A process evaluation of the implementation of a mobile phone-supported intervention after stroke in Uganda

Abstract: Background The prevalence of stroke in Uganda is increasing. In stroke rehabilitation, information and communication technology has been shown to have potential in improving service delivery in high-income countries but there is limited knowledge of its use and impact in low-income countries. The aim of the study was to evaluate the implementation process of a mobile phone-supported family-centred rehabilitation intervention and to gain knowledge on the mechanisms of impact as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(99 citation statements)
references
References 23 publications
0
99
0
Order By: Relevance
“…We identified how public contributors and lay communities are not only recipients of healthcare innovations but also have potential to be powerful facilitators of implementation, thus illustrating the overlap between the recipient and facilitation constructs of i-PARIHS. Similarly, authors of a process evaluation of the implementation of a mobile phone supported intervention after stroke [ 57 ] suggested that the word recipient may emphasise a slightly more passive role for those involved in the implementation process and renamed the recipient construct of i-PARIHS to ‘implementers’.…”
Section: Discussionmentioning
confidence: 99%
“…We identified how public contributors and lay communities are not only recipients of healthcare innovations but also have potential to be powerful facilitators of implementation, thus illustrating the overlap between the recipient and facilitation constructs of i-PARIHS. Similarly, authors of a process evaluation of the implementation of a mobile phone supported intervention after stroke [ 57 ] suggested that the word recipient may emphasise a slightly more passive role for those involved in the implementation process and renamed the recipient construct of i-PARIHS to ‘implementers’.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the effectiveness and comparative effectiveness is available for many health conditions [61][62][63][64]. The use of telehealth provides increased access, equity, and outreach for rehabilitation services, including for people in rural or remote communities of either high-or low-income nations [65][66][67][68][69][70]. This new increase in demand creates an unprecedented opportunity to scale up the practitioners' habits and capabilities for the use of this service delivery form, as well as scale up the system's capacity (e.g.…”
Section: Leaver #4: Embracing the Added Emphasis On And Capacity For mentioning
confidence: 99%
“…The remaining nine studies only identi ed barriers & facilitators. The second most utilized discrete strategy was [16] Conduct educational outreach visits implemented by ten studies (36,39,41,43,45,46,(48)(49)(50)(51). Other frequently used discrete strategies include [19] Conduct ongoing training, [5] Audit & provide feedback, and [29] Develop educational materials, each of which was implemented in eight of the studies.…”
Section: Synthesis Summarymentioning
confidence: 99%
“…The studies also frequently utilized discrete implementation strategies from the following two clusters: use evaluative and iterative strategies and develop stakeholder interrelationships. Seventeen studies implemented strategies in the evaluative and interactive strategies cluster (40,42,(44)(45)(46)(47)(48)(49)(51)(52)(53)(54)(55)(56)(57)(58)(59), with [4] Assess for readiness & identify barriers & facilitators being implemented the most within this cluster. Discrete strategies from the develop stakeholder relationships cluster were used in 12 studies (37,39,40,43,44,46,49,50,52,56,60,61), with [35] Identify & prepare champions being implemented the most with 7 studies (39,43,44,46,49,56,61).…”
Section: Synthesis Summarymentioning
confidence: 99%